Advances in point-contact spectroscopy: two-band superconductor MgB₂ (Review Article) - Yanson, I.K.; Naidyuk, Yu.G. (Физика низких температур, 2004)
Analysis of the point-contact spectroscopy (PCS) data on the new dramatic high-Tc superconductor
magnesium diboride MgB₂ reveals quite different behavior of two disconnected σ and π electronic
bands, deriving from their anisotropy, different dimensionality, and electron—phonon interaction.
PCS allows direct registration of both the superconducting gaps and electron—phonon
interaction spectral function of the two-dimensional σ and three-dimensional π band, establishing
correlation between the gap value and intensity of the high-Tc driving force — the E₂g boron vibration
mode. PCS data on some nonsuperconducting transition-metal diborides are surveyed for comparison.